ANALYSIS OF FACTORS AFFECTING FINANCIAL LITERACY AND FINANCIAL INCLUSION ON INSTITUT BISNIS DAN TEKNOLOGI PELITA INDONESIA PEKANBARU - Silvilia Iman Sari; Mimelientesa Irman; Evelyn Wijaya (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
Having knowledge and doing financial planning is a process of achieving life goals, namely a prosperous and happy future through financial management. Financial inclusion cannot be separated from the extent to which the public can understand financial products/services so that they are able to use them in providing value for welfare. This study aims to examine whether the factors of gender, age, and GPA affect the level of financial literacy and financial inclusion among students at the Pelita Indonesia Institute of Business and Technology Pekanbaru. The respondents studied were 95 students. The method used in this research is descriptive method and test method. To obtain the required data, data collection in the form of a questionnaire was used. In this study, the type of data used is primary data. Based on the Binary Logistics Test, the results of the study show that the factors of gender, age, and GPA have no effect on the level of financial literacy of a student at the Pelita Indonesia Institute of Business and Technology Pekanbaru, gender and age factors do not affect the level of financial inclusion of a student. Pelita Indonesia Institute of Business and Technology Pekanbaru, while GPA and financial literacy affect the level of financial inclusion of a student at the Pelita Indonesia Institute of Business and Technology Pekanbaru.